Compassion and the Characterization of the Markan Jesus - Bryant, Jonathan (Biblical interpretation series, 2024)
This volume discusses the role of compassion in the portrayal of the Markan Jesus, reshaping our view of his encounters with human need. It analyzes the depictions of miracle workers from the ancient world and underscores Mark's portrayal as exceptional.